2018
DOI: 10.1038/s41598-018-31989-z
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature synthesis of NbC/C nano-composites as visible light photoactive catalyst

Abstract: A facile carbothermal route was adopted to obtain niobium carbide nanoparticles (NPs) embedded in carbon network from Nb2O5 to study photocatalytic behavior. Optimization of synthesis parameters to obtain single phase NbC NPs has been successfully done. The phase identification, morphology and nature of carbon were determined with the help of X-ray diffraction, transmission electron microscopy (TEM) and Raman spectroscopy. X-ray photoelectron spectroscopy (XPS) suggested the presence of multiple oxidation stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(28 citation statements)
references
References 79 publications
4
24
0
Order By: Relevance
“…Whereas in the presence of the nanohybrid catalyst, the LC−MS spectra obtained during the course (time intervals 0−5 min) of the reaction showed gradual fragmentation of peaks and led to small molecules of 74 and 81 Da at the end of the reaction. The possible degradation products are provided in Figure S12 of the Supporting Information, and the observed fragmentation molecules match well with the previous reports. …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Whereas in the presence of the nanohybrid catalyst, the LC−MS spectra obtained during the course (time intervals 0−5 min) of the reaction showed gradual fragmentation of peaks and led to small molecules of 74 and 81 Da at the end of the reaction. The possible degradation products are provided in Figure S12 of the Supporting Information, and the observed fragmentation molecules match well with the previous reports. …”
Section: Resultssupporting
confidence: 89%
“…The possible degradation products are provided in Figure S12 of the Supporting Information , and the observed fragmentation molecules match well with the previous reports. 53 56 …”
Section: Resultsmentioning
confidence: 99%
“…The NbC precipitates contribution is found again on the Nb 3d spectra (Figs.2g and 3g) convoluted with other Nb oxide species due to spin-orbit split ting (�E Nb 3d � 2.7 eV)[50]. Gupta et al demonstrated that NbC compounds present complex oxide layers at different oxidation degrees in the case of NbC nanocomposites[51]. Based on this work, the Nb 3d spectra were decomposed in three components (six peaks for 3d 5 1 2 and 3d 3 ; 2 ) corresponding respectively to NbC precipitates at lower BE values, a mixture of carbide-oxide NbCxO y and Nb 1v 0 2 oxide at higher BE values for all samples studied.…”
mentioning
confidence: 87%
“…Both contributions can be found in all CO/H 2 treated films, indicating that regardless of the initial iron oxide phase, a significant contribution of a carbide phase in the surface region can be deduced. Except for the contributions assigned to iron carbides and iron oxide, several prominent features in the spectra can be assigned to graphitic carbon (284.8 eV), surface hydroxylated carbon (286.3 eV) and surface oxidation (298.1 eV) in every C 1s spectra [34,35]. In the O 1s spectrum, two peaks assignable to C-O (531.9 eV) and -OH (533.1 eV) can be observed and are well-known from other iron oxide materials [36].…”
Section: Review 4 Of 11mentioning
confidence: 99%